1989
DOI: 10.1097/00000658-198901000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with the EEA Stapling Technique for Esophagojejunostomy after Total Gastrectomy

Abstract: Since November 1980, the EEA stapling device has been used to create an end-to-side esophagojejunostomy in 238 patients who underwent total gastrectomy. Failures in the stapling technique were divided into two groups: immediate and delayed. Immediate failures were observed and corrected at the time of surgery. In ten cases, the muscular layer of the esophagus was disrupted, and in three the mucosal layer of the jejunum was disrupted. There were 18 delayed complications: eight cases of anastomotic leakage (3.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 8 publications
1
38
0
5
Order By: Relevance
“…These instruments permit procedures such as total gastrectomy and low anterior colorectal resection, lengthy operations previously associated with a high incidence of complications, to be done relatively safely. Mechanical staplers have shortened the operation time, facilitated the performance of gastrointestinal anastomoses at sites with a poor field of view, and lowered the likelihood of suture failure [1][2][3]. Several prospective, randomized controlled studies have compared hand suturing with mechanical stapling in patients undergoing total gastrectomy and low anterior colorectal resection [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These instruments permit procedures such as total gastrectomy and low anterior colorectal resection, lengthy operations previously associated with a high incidence of complications, to be done relatively safely. Mechanical staplers have shortened the operation time, facilitated the performance of gastrointestinal anastomoses at sites with a poor field of view, and lowered the likelihood of suture failure [1][2][3]. Several prospective, randomized controlled studies have compared hand suturing with mechanical stapling in patients undergoing total gastrectomy and low anterior colorectal resection [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Even recent studies have not reported a leakage rate of less than 1% for esophagojejunostomy. 9,10 The lowest reported leakage rates were 1% among 588 patients treated at the National Cancer Institute in Japan 7 and 1.35% among 148 patients in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, circular staplers have been used since the 1980s which offer several advantages in terms of safety and feasibility over conventional techniques for esophagojejunostomy after total gastrectomy. [4][5][6] Worldwide, stapler devices have been used Patients who underwent a stapled esophagojejunostomy anastomosis were divided into two groups. In Group A (n=30), a 28-mm-diameter stapling device was used whereas group B (n=30) a 25-mm-diameter stapler was used in esophagojejunostomy anastomosis.…”
mentioning
confidence: 99%
“…Apesar da popularização da anastomose mecânica esôfago-jejunal término-lateral, em decorrência da sua rapidez de execução e da baixa incidência de fístulas, ainda persistem problemas técnicos e restrições econômicas 4 . Podem ocorrer dificuldades de utilização do grampeador circular, representadas por fragilidade do esôfago, decorrente ou não da desvascularização do órgão, bem como da desproporção entre o calibre do grampeador e do diâmetro interno do tubo digestivo.…”
Section: Comentáriosunclassified